Clinical Characteristics of Primary Hyperparathyroidism: 15-Year Experience of 457 Patients in a Single Center in China - Lin, Xiaoyun; Fan, Youben; Zhang, Zhenlin; Yue, Hua (Frontiers in Endocrinology, 2021)
Objective: Primary hyperparathyroidism (PHPT) is a common endocrine disorder of calcium metabolism. However, data concerning a large cohort of PHPT patients in the Chinese population are scarce. Thus, the objective of this study was to determine the general clinical signatures of 457 Chinese PHPT patients and explore the clinical characteristic differences between benign and malignant PHPT. Methods: A single-center retrospective study was designed. Medical records between preoperation and postoperative follow-up, were assessed and statistical analysis of the clinical data was performed. Results: Patients with PHPT aged 12–87 years, with a mean onset age of 56.16±14.60 years, were included. Most patients (68.7%) in our center had symptomatic patterns described as bone pain (74.8%), urolithiasis (25.5%), fatigue (17.5%) and pathological fracture (13.1%), but an increasing tendency has been established in the proportion of patients with asymptomatic forms. Correlation analysis revealed that patients with higher serum levels of parathyroid hormone (PTH) and calcium presented higher serum levels of bone metabolism markers and lower 25-hydroxy-vitamin D (25OHD) values (P<0.001). Gains in bone mineral density (BMD) at L1–4, the femoral neck and the total hip were observed 1–2 years after parathyroidectomy (9.6%, 5.9% and 6.8%). Parathyroid carcinoma patients presented prominently higher serum PTH and calcium levels and bone turnover markers (BTMs) and lower BMD at femoral neck and total hip than benign PHPT patients (P<0.05), while no significant differences in age, sex, and serum 25OHD concentration were observed between benign and malignant PHPT patients. Conclusions: PHPT should be paid attention to in the patients with bone pain. While, BMD and BTMs can differentiate parathyroid carcinoma from parathyroid adenoma and hyperplasia to some extent. In addition, anti-osteoporosis drugs could be used when necessary to avoid hip fractures in patients with parathyroid carcinoma.